2021
DOI: 10.1037/adb0000762
|View full text |Cite
|
Sign up to set email alerts
|

Initial efficacy of a web-based alcohol and emotion regulation intervention for college women with sexual assault histories.

Abstract: Objective: College women with sexual assault histories report greater heavy drinking relative to those without histories of assault. Moreover, individuals with sexual assault histories often have difficulty regulating emotions and tolerating distress, which can lead to a problematic pattern of drinking to cope. Thus, we evaluated the initial efficacy of a web-based alcohol intervention that included strategies to reduce drinking and improve regulatory skills for heavy drinking college women with sexual assault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 77 publications
2
18
0
1
Order By: Relevance
“…Of significance, our qualitative findings add to the literature on how to build on the strengths of undocumented immigrants during a politically charged climate. Specifically, the web-based skills program implemented aligns with research on the effectiveness of web-based skills programs in the reduction of trauma symptoms as well as improvement in emotion regulation skills for individuals with a history of trauma (Stappenbeck et al, 2021). Finally, the discussed program calls attention to the need for new theoretical models of digital community healing spaces and interventions for vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of significance, our qualitative findings add to the literature on how to build on the strengths of undocumented immigrants during a politically charged climate. Specifically, the web-based skills program implemented aligns with research on the effectiveness of web-based skills programs in the reduction of trauma symptoms as well as improvement in emotion regulation skills for individuals with a history of trauma (Stappenbeck et al, 2021). Finally, the discussed program calls attention to the need for new theoretical models of digital community healing spaces and interventions for vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the interactive effect with gender indicates the childhood victimization's effect is stronger (in generating heavy drinking risk) for female adolescents than for male adolescents for whom a decrease in risk was observed. Previous literature suggests that women's experiences with sexual assault may be leading to differences in levels of psychological distress as well as later heavy drinking behavior [54,55]. Traumatic events early in the lifespan may forge a critical link in a chain of events leading to psychological distress (e.g., depression) to adult alcohol use or other substance use [51,87].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the effectiveness of brief motivational interventions or motivational interviews on drinking behavior, and these could be further refined to reach broader audiences, including adolescent and young women who are heavy drinking [17,18,63]. Another option that focuses on low-cost levels is text message or webbased programming aimed at reducing heavy drinking episodes or behaviors, which has demonstrated some effectiveness thus far in the literature for younger populations [54,99]. Promising approaches exist for treatment of heavy drinking behavior, and greater research and funding into both medical and other modalities would promote health equity in the United States and globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many DAFSV behaviors do not meet legal definitions for sexual assault or domestic violence, and many individuals may not identify their experiences as such, this type of victimization may go undetected in clinical care settings despite its association with various indicators of mental health (i.e., depression and anxiety symptoms) and well-being (i.e., selfesteem, loneliness, perceived control). Further, given the online context of DAFSV, web-based prevention and intervention may be particularly accessible and effective for victims and could concurrently be used to address intersecting health concerns such as heavy drinking (Gulati et al, 2021;Stappenbeck et al, 2021).…”
Section: Implications and Conclusionmentioning
confidence: 99%